Building Loyalty in Finance: The Interplay of Brand Image, Communication, Service Quality, and Trust - Emilia, Lynda; Ratnawati, Alifah (ProBisnis : Jurnal Manajemen, 2025)
This research aims to investigate the impact of brand image, brand communication, and service quality on user loyalty, with trust serving as a mediating factor in the context of finance companies in Sragen Regency. This study uses a quantitative approach with a survey technique on 101 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the investigation indicate that brand image and brand communication have a significant positive impact on trust. Brand image also has a significant direct impact on user loyalty. Trust has a significant impact on user loyalty, but does not mediate the relationship between brand image, brand communication, or service quality on loyalty. Meanwhile, service quality does not have a significant effect on trust or loyalty. These findings indicate that in the context of finance companies, brand image and trust play an important role in building user loyalty, while service quality has not been the main determinant.  This research introduces a contextualized and empirically grounded perspective on customer loyalty, offering theoretical implications by questioning mediation pathways and practical guidance for financial institutions to prioritize brand and trust-building strategies over conventional service enhancement alone.